The Dopamine and Cannabinoid Interaction in the Modulation of Emotions and Cognition: Assessing the Role of Cannabinoid CB1 Receptor in Neurons Expressing Dopamine D1 Receptors - Terzian, Ana Luisa; Drago, Filippo; Wotjak, Carsten T.; Micale, Vincenzo (Frontiers in Behavioral Neuroscience, 2011)
Although cannabinoid CB1 receptors (CB1Rs) are densely expressed in neurons expressing dopamine D1 receptors (D1Rs), it is not fully understood to what extent they modulate emotional behaviors. We used conditional CB1R knock-out animals lacking CB1Rs in neurons expressing D1R (D1-CB1-/-) in order to answer this question. To elucidate the behavioral effects of CB1R deficiency in this specific neuronal subpopulation, we subjected D1-CB1-/- mice to a battery of behavioral tests which included exploration-based tests, depressive-like behavioral tests, social behavior and fear-related memory paradigms. D1-CB1-/- did not show any difference in the exploration-based paradigms such as open field, elevated plus maze or novel object investigation test, except for an increase in novelty-induced grooming. By contrast, they showed a mild anhedonia-like state as described by the slightly decreased preference for sweet solution, as compared to wild-type control (WT) group. This decrease, however, could be observed only during the first day of exposure, thus suggesting increased neophobia as an alternative explanation. Accordingly, mutant mice performed normally in the forced swim test, a procedure widely used for evaluating behavioral despair in rodents. However, weak- to moderate anxiety-like phenotypes were evident when D1-CB1-/- mice were tested for social behavior. Most strikingly, D1-CB1-/- mice exhibited significantly increased contextual and auditory-cued fear, with attenuated within session extinction, suggesting that a specific reduction of endocannabinoid signaling in neurons expressing dopamine D1Rs is able to affect acute fear adaptation. These results provided first direct evidence for a cross-talk between dopaminergic D1Rs and endocannabinoid system in terms of controlling negative affect.